2009
DOI: 10.1364/ol.34.003917
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-image encryption and multiplexing using a modified Gerchberg-Saxton algorithm and phase modulation in Fresnel-transform domain

Abstract: What we believe to be a new technique, based on a modified Gerchberg-Saxton algorithm (MGSA) and a phase modulation scheme in the Fresnel-transform domain, is proposed to reduce cross talks existing in multiple-image encryption and multiplexing. First, each plain image is encoded and multiplexed into a phase function by using the MGSA and a different wavelength/position parameter. Then all the created phase functions are phase modulated to result in different shift amounts of the reconstruction images before b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
124
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 10 publications
0
124
0
Order By: Relevance
“…The published results by H. E. Hwang et al [14], show a maximum number of GL images, N=10, and illustrate an evident decreasing of correlation coefficient (CC) quality factor when increasing the N image number, obtaining an approximately value CC=0.93 for N=10. Other case to consider is the work by H. T. Chang et al [15], in which they evaluate the CC factor vs the N number of images in the multiplexed package, reaching a quality value CC=0.82 for N=9.…”
Section: Introductionmentioning
confidence: 97%
“…The published results by H. E. Hwang et al [14], show a maximum number of GL images, N=10, and illustrate an evident decreasing of correlation coefficient (CC) quality factor when increasing the N image number, obtaining an approximately value CC=0.93 for N=10. Other case to consider is the work by H. T. Chang et al [15], in which they evaluate the CC factor vs the N number of images in the multiplexed package, reaching a quality value CC=0.82 for N=9.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the encryption capacity is also limited in these encryption methods. To overcome the cross-talk problem and increase encryption capacity, many improved multiple-image encryption techniques have been proposed [14][15][16][17][18][19][20][21]. In the encryption process of these improved methods, all images to be encrypted are required to be encoded separately into one or more phase-only masks with all kinds of phase retrieval algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the above improved multiple-image encryption method based on all kinds of phase retrieval algorithm [14][15][16][17][18][19][20][21], in our method all images to be encrypted also are first encoded separately into a phase-only image with the help of the fully phase encoding in computer. Then these phase-only images are intermodulated into a single phase-only image by multiplication.…”
Section: Introductionmentioning
confidence: 99%
“…Deng and Zhao 21 suggested a multiple-image encryption by using a phase retrieval algorithm and intermodulation in the Fourier domain, which avoids the cross-talk of decrypted images. Hwang et al 22 proposed a multiple-image encryption and multiplexing approach based on a modified GerchbergSaxton algorithm (MGSA) in the FrT domain, which reduces the cross-talks significantly. Chang et al 23,24 also suggested the position multiplexing encryption using cascaded phaseonly masks based on the MGSA.…”
Section: Introductionmentioning
confidence: 99%